Features of Conflicts in the Pedagogical Team - Ivaylo Ivanov (Педагогически форум)
The publication examines the nature, functions and causes of occurrence of conflicts in the pedagogical team. The attitude of pedagogical specialists to conflicts in their professional activities has been studied. The interpersonal relationships between teachers in the pedagogical college were analyzed.